STING single amino acid polymorphisms modulate iridovirus immune evasion and pathogenicity spectrum - Xiaowei Qin; Mincong Liang; Weiqiang Pan; Zhipeng Zhan; Chuanrui Li; Yanlin You; Shaoping Weng; Jianguo He; Changjun Guo (Proceedings of the National Academy of Sciences, 2026)
The evolutionary arms race between viruses and hosts shapes host antiviral defenses and viral immune evasion, yet the mechanisms driving divergence in viral cross-species pathogenicity remain unclear. Here, we investigated the role of single amino acid polymorphisms (SAPs) in stimulator of interferon genes (STING) in modulating immune evasion and pathogenicity spectrum of infectious spleen and kidney necrosis virus (ISKNV). The ISKNV-encoded protein VP012R targets mandarin fish STING ( sc STING) for ubiquitination at residues C196 and K315, promoting its degradation to suppress interferon responses. Importantly, the K315/R315 polymorphism acts as a molecular switch: Susceptible species with the K315 residue exhibit STING degradation and viral immune evasion, whereas resistant species with the R315 residue maintain STING stability and antiviral defenses. Phylogenetic analysis linked K315 to high-mortality hosts (≥50% lethality) vs. R315 in resistant species (≤25% lethality). These findings suggest that the molecular mechanisms underlying the viral pathogenicity spectrum may be modulated by host protein SAPs, thereby enhancing our understanding of host–virus coevolution in terms of biological diversity.